Comprehensive Analysis of 5-Methylcytosine (m5C) Regulators and the Immune Microenvironment in Pancreatic Adenocarcinoma to Aid Immunotherapy - Wang, Ronglin; Guo, Yongdong; Ma, Peixiang; Song, Yang; Min, Jie; Zhao, Ting; Hua, Lei; Zhang, Chao; Yang, Cheng; Shi, Jingjie; Zhu, Liaoliao; Gan, Dongxue; et al. (Frontiers in Oncology, 2022)
Background: Pancreatic adenocarcinoma (PAAD) is one of the most malignant cancers and has a poor prognosis. As a critical RNA modification, 5-methylcytosine (m5C) has been reported to regulate tumour progression, including PAAD progression. However, a comprehensive analysis of m5C regulators in PAAD is lacking. Methods: In the present study, PAAD datasets were obtained from the Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), and ArrayExpress databases. The expression pattern of m5C regulators were analysed and patients were divided into different m5C clusters according to consensus clustering based on m5C regulators. Additionally, m5C differentially expressed genes (DEGs) were determined using Limma package. Based on m5C DEGs, patients were divided into m5C gene clusters. Moreover, m5C gene signatures were derived from m5C DEGs and a quantitative indicator, the m5C score, was developed from the m5C gene signatures. Results: Our study showed that m5C regulators were differentially expressed in patients with PAAD. The m5C clusters and gene clusters based on m5C regulators and m5C DEGs were related to immune cell infiltration, immune-related genes and patient survival status, indicating that m5C modification play a central role in regulating PAAD development partly by modulating immune microenvironment. Additionally, a quantitative indicator, the m5C score, was also developed and was related to a series of immune-related indicators. Moreover, the m5C score precisely predicted the immunotherapy response and prognosis of patients with PAAD. Conclusion: In summary, we confirmed that m5C regulators regulate PAAD development by modulating the immune microenvironment. In addition, a quantitative indicator, the m5C score, was developed to predict immunotherapy response and prognosis and assisted in identifying PAAD patients suitable for tailored immunotherapy strategies.